Comparison of associations suggests mainly distinct pools of genetic risk factors contribute to cisplatin-induced hearing loss and hearing difficulty in the general population - Mohammad Shahbazi; Heather E. Wheeler; Xindi Zhang; Robert D. Frisina; Lois B. Travis; M. Eileen Dolan (Frontiers in Pharmacology)
Cisplatin is an effective chemotherapeutic agent for treating many cancers. However, a major complication associated with cisplatin treatment is ototoxicity. Since the early 2000s, several genetic risk factors linked to cisplatin ototoxicity have been reported. However, the extent to which these genetic risk factors might be shared with those contributing to hearing difficulty in the general population remains unknown. In this study, we investigate if variants with reported links to increased risk of ototoxicity in cisplatin-treated cancer cohorts were also associated with hearing impairment in the general population in the results from a recent meta-analysis (Meta-study; 501,825 participants). Importantly, no significant associations were identified. We also compared association results from our recent genome-wide association study (GWAS) for hearing loss in male testicular cancer survivors (Pt-study; 1,071 participants) with those from both Meta-study and a meta-analysis of the male subset (Male-study; 223,081 participants). We observed evidence for colocalization at the rs7952909 locus across the Male-study and Pt-study results, however, with opposite directions of effects. Across pairwise comparisons, only two variants with matching directions of effects reached significance when relaxed selection cutoffs (10−3 or 10−4) were used. Collectively, our results suggest that genetic risk factors for cisplatin-induced ototoxicity and those for hearing difficulty in the general population are largely distinct.